Fiqhul Lughah : Studi Historis Perkembangan Bahasa Semit dan Evolusi Bahasa Arab (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
The Semitic language family is one of the oldest linguistic groups that has significantly influenced world civilizations, with Arabic as one of its main branches. Arabic has undergone a long historical journey from prehistoric times to the modern era, shaped by various historical, cultural, and social factors. The study of Fiqhul Lughah, or the philosophy of language, is crucial in understanding the transformation and development of Arabic in different historical contexts. This research employs a library research method, analyzing various literary sources such as books, scholarly journals, and ancient manuscripts that discuss the history and evolution of Semitic languages, particularly Arabic. The analysis is conducted using a descriptive-qualitative approach to comprehend the patterns of Arabic evolution from its ancient Semitic roots to its establishment as a major language in communication, literature, science, and religion. The findings indicate that Arabic has evolved gradually through various historical phases, from its pre-classical stage to the golden age of Islam and its modern adaptations. Understanding the history and classification of Arabic within the Semitic language family provides deeper insights into its dynamics and its significant role in shaping human civilization.